Damp mouldy housing and early childhood hospital admissions for acute respiratory infection: a case control study. Issue 9 (14th August 2019) - Ingham, Tristram; Keall, Michael; Jones, Bernadette; Aldridge, Daniel R T; Dowell, Anthony C; Davies, Cheryl; Crane, Julian; Draper, Jessica Barbara; Bailey, Lauren Olivia; Viggers, Helen; Stanley, Thorsten Villiers; Leadbitter, Philip; et al.
Abstract : Introduction: A gap exists in the literature regarding dose–response associations of objectively assessed housing quality measures, particularly dampness and mould, with hospitalisation for acute respiratory infection (ARI) among children. Methods: A prospective, unmatched case–control study was conducted in two paediatric wards and five general practice clinics in Wellington, New Zealand, over winter/spring 2011–2013. Children aged <2 years who were hospitalised for ARI (cases), and either seen in general practice with ARI not requiring admission or for routine immunisation (controls) were included in the study. Objective housing quality was assessed by independent building assessors, with the assessors blinded to outcome status, using the Respiratory Hazard Index (RHI), a 13-item scale of household quality factors, including an 8-item damp–mould subscale. The main outcome was case–control status. Adjusted ORs (aORs) of the association of housing quality measures with case–control status were estimated, along with the population attributable risk of eliminating dampness–mould on hospitalisation for ARI among New Zealand children. Results: 188 cases and 454 controls were studied. Higher levels of RHI were associated with elevated odds of hospitalisation (OR 1.11/unit increase (95% CI 1.01 to 1.21)), which weakened after adjustment for season, housing tenure, socioeconomic status and crowding (aOR 1.04/unit increase (95% CI 0.94 to 1.15)). The damp–mould index had a significant, adjusted dose–response relationship with ARI admission (aOR 1.15/unit increase (95% CI 1.02 to 1.30)). By addressing these harmful housing exposures, the rate of admission for ARI would be reduced by 19% or 1700 fewer admissions annually. Conclusions: A dose–response relationship exists between housing quality measures, particularly dampness–mould, and young children's ARI hospitalisation rates. Initiatives to improve housing quality and to reduce dampness–mould would have a large impact on ARI hospitalisation.